Internalizing Qur’anic Tolerance through Al-Kafirun 6 and Al-Baqarah 256 to Shape Students’ Religious Moderation - Alpina, Weny; Khosiin, Khamam; Syahrin, Muhmammad Alfi (Yayasan Adra Karima Hubbi, 2025)
Background. Religious diversity in contemporary societies, particularly in Indonesia, presents challenges related to intolerance, exclusivist religious interpretations, and identity-based tensions among students. Islamic educational institutions play a strategic role in addressing these challenges by internalizing Qur’anic values that promote tolerance and religious moderation. Purpose. This study aims to explore how Qur’anic values of tolerance derived from Al-Kafirun verse 6 and Al-Baqarah verse 256 are internalized in shaping students’ religious moderation at SMK Muhammadiyah Berau. Method. This research employed a qualitative case study design. Data were collected through in-depth interviews, classroom and school observations, and document analysis involving Islamic education teachers, school leaders, and students. The data were analysed using an interactive qualitative model consisting of data reduction, data display, and conclusion drawing. Results. The findings reveal that the internalization of Qur’anic tolerance operates through the integration of institutional policies, pedagogical practices, and students’ lived experiences. Qur’anic values are embedded in school regulations, dialogical teaching approaches, character education programs, and daily social interactions. Supporting factors include strong school leadership, inclusive school culture, and teacher role modeling, while challenges arise from external influences such as social media and diverse family backgrounds. Conclusion. The study demonstrates that consistent and inclusive internalization of Qur’anic teachings effectively fosters students’ religious moderation without weakening Islamic identity. These findings highlight the importance of integrating Qur’anic values into school culture and pedagogy as a strategic approach to promoting social harmony in pluralistic educational contexts.